2024
DOI: 10.1584/jpestics.d23-052
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of allelochemicals and their activities and functions

Hisashi Kato-Noguchi

Abstract: Allelopathy is the interaction between donor plants and receiver plants through allelochemicals. According to a great number of publications, allelopathy may be involved in several ecological aspects such as the formation of monospecific stands and sparse understory vegetation for certain plant species. Allelopathy also contributes to the naturalization of invasive plant species in introduced ranges. Autotoxicity is a particular type of allelopathy involving certain compounds. Many medicinal plants have been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 126 publications
0
1
0
Order By: Relevance
“…Many researchers have recently reported that the growth of test plant species, including weeds, was inhibited by the phytotoxic substances found in medicinal plants [24][25][26]. Kato-Noguchi (2023) [27] reported that many medicinal plants are highly allelopathic and have yielded over 100 allelochemicals, including novel compounds that exhibit different levels of biological activities and functions. These findings showed that medicinal plants contain different kinds of phytotoxic substances that could exert allelopathic activity, and these plants are probable candidates that could be used to isolate and identify potent allelopathic substances that can be used as bioherbicides for sustainable weed management.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have recently reported that the growth of test plant species, including weeds, was inhibited by the phytotoxic substances found in medicinal plants [24][25][26]. Kato-Noguchi (2023) [27] reported that many medicinal plants are highly allelopathic and have yielded over 100 allelochemicals, including novel compounds that exhibit different levels of biological activities and functions. These findings showed that medicinal plants contain different kinds of phytotoxic substances that could exert allelopathic activity, and these plants are probable candidates that could be used to isolate and identify potent allelopathic substances that can be used as bioherbicides for sustainable weed management.…”
Section: Introductionmentioning
confidence: 99%